MACROECONOMIC NEWS, AND MANAGEMENT FORECAST - Lin, Guoyu (International Journal of Accounting & Finance Review, 2022)
Do companies whose earnings move more with macroeconomy more likely or less likely to offer management forecasts? This paper documents the following findings: (1) there is a significantly positive relationship between the extent to which a company’s earnings move in concert with GDP and the likelihood of issuing management forecasts. The explanation is that, if a firm’s earnings move in concert with GDP, then the cost of missing management forecasts is lower as managers could blame this on the wrong forecasts of macro news, instead of firm-specific forecasts. It contributes to the burgeoning literature on macro-accounting by first documenting this channel. Also, on top of R-square, which has been used in the literature on macro-accounting, this paper suggests that the coefficient and p-value from the regressions of firms’ earnings on GDP, is useful in helping identify bellwether firms (firms with high macroeconomic information content or firms connected to many other firms in the economy). JEL Classification Codes: B17, B22, E27.